Altering perceptions of child sexual abuse survivors and individuals with dissociative identity disorder - Norval, Sara Marie (Kansas State University, 2015)
At 47 years old, Lori is a high-functioning businesswoman, matriarch, and contributing member of society. Lori is also diagnosed with Dissociative Identity Disorder (DID). From age 3, Lori was violently raped and assaulted by several perpetrators, yet views her multiple personalities as strength, as survival mechanisms, and wants to share her story to help prevent child sexual abuse. Utilizing methods drawn from communication studies, ethnodrama, and autoethnography, this study aims to tell a person’s story in her own words and in a format that can easily be shared with both academic and non-academic audiences. Lori’s story is woven together as an ethnodramatic play that includes original interview transcripts along with an autoethnographic monologue describing the experience of writing someone’s truth when it challenges the hegemonic views of society, and instead embraces the feminist ideals of equality and deconstruction of power. Academic research needs to reach further than academic journals to make a true impact. Through the non-conventional venues of autoethnography and ethnodrama, we can breathe life into our research and provide accessibility to innovative information for those who may need it most.
Keywords: Ethnodrama; Autoethnography; Ethnography; Ethnographic Fiction; Dissociative Identity Disorder; Child Sexual Abuse; Communication (0459)